2012
DOI: 10.4018/ijabe.2012070104
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Training, Job Satisfaction, and Corporate Brand Image Relationship to Employees Working Performance in Context of British American Tobacco, Dhaka

Abstract: This paper examines the relationship of training, job satisfaction, and corporate brand image with employees working performance at British American Tobacco, Dhaka. A significant relationship exists between training and employees’ performance at BAT Dhaka in Bangladesh. To produce better work efforts, it is important to note that job satisfaction influences satisfactory performance output. It is found that brand image psychologically influences and motivates employees and is strongly related to employees worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…According to Jago and Deery (2004), the internal labor market consists of training, job security and promotional opportunity, which are all significantly related to turnover intention. A recent empirical study has shown strong relationships between training, job satisfaction, job performance, morale and eventually job commitment (Chowdhury, Hira, Mamun, & Kaisar, 2012). Where strong barriers exist in these three components, turnover intention may be high.…”
Section: Controllable Factorsmentioning
confidence: 99%
“…According to Jago and Deery (2004), the internal labor market consists of training, job security and promotional opportunity, which are all significantly related to turnover intention. A recent empirical study has shown strong relationships between training, job satisfaction, job performance, morale and eventually job commitment (Chowdhury, Hira, Mamun, & Kaisar, 2012). Where strong barriers exist in these three components, turnover intention may be high.…”
Section: Controllable Factorsmentioning
confidence: 99%